2014
DOI: 10.1007/s00405-014-3206-0
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear re-implant rates in children: 20 years experience in a quaternary paediatric cochlear implant centre

Abstract: The aim of this study is to determine the incidence and causes for cochlear explantation/re-implantation in children as a retrospective case review in a Quaternary paediatric Cochlear Implant (CI) Centre. The subjects included in the study were Paediatric CI patients requiring cochlear explantation/re-implantation. Outcome measurements were incidence and aetiology of device explantation/re-implantation. Patient age at implantation, aetiology of deafness, CI manufacturer, and timing of explantation/re P implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Long study periods are by default more recent publications. It is evident that higher numbers of both children and children receiving bilateral implants occur in the later study period [20][21][22] (only unilateral implants were provided up to the early 2000s). With this 'implants -v-time' profile the results of such studies will be biased by the large number of newer implants with a short duration of use even when total study length is 20 years or more.…”
Section: Results From Long Study Periodsmentioning
confidence: 99%
“…Long study periods are by default more recent publications. It is evident that higher numbers of both children and children receiving bilateral implants occur in the later study period [20][21][22] (only unilateral implants were provided up to the early 2000s). With this 'implants -v-time' profile the results of such studies will be biased by the large number of newer implants with a short duration of use even when total study length is 20 years or more.…”
Section: Results From Long Study Periodsmentioning
confidence: 99%
“…In the literature, the rate of implants required revision surgery was reported to be between 3.6% and 11%. [4][5][6][7][8] In the current study, 4% of total Revised cochlear implant surgeries ... Aldhafeeri et al Table 1 -Summary of revision cases based on implant companies. cochlear implanted patients underwent revision surgery.…”
Section: Brief Communicationmentioning
confidence: 66%
“…2,4 Overall reported incidence rates for CIR fall between 3% and 13%, with slightly higher rates among children than adults (5%-13%). [2][3][4][5]7,[13][14][15] CIR may be motivated by a number of factors, including hard device failure (patient performance declines secondary to malfunction of the internal device), soft failure (patient performance declines in the absence of identifiable device malfunction), trauma (e.g., blow to the head), or medical complications (e.g., infection, migration of the internal device). 1-3,7,13 From a group of 60 patients undergoing CIR, Donatelli Lassig et al 1 describe 10 patients who reported technology upgrade as a primary reason for undergoing revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors acknowledge technological upgrade as a possible reason for CIR but do not report on any cases in this category . Overall reported incidence rates for CIR fall between 3% and 13%, with slightly higher rates among children than adults (5%–13%) . CIR may be motivated by a number of factors, including hard device failure (patient performance declines secondary to malfunction of the internal device), soft failure (patient performance declines in the absence of identifiable device malfunction), trauma (e.g., blow to the head), or medical complications (e.g., infection, migration of the internal device) .…”
Section: Discussionmentioning
confidence: 99%